Number 13 / Part I. Music. 10. Communicational Entropy in The Present's Crisis - Mediation and Community Action through Music Management - Balan Oana (Sciendo, 2017)
Present day art phenomena that surround us from all media channels compel us, who have been educated as professional musicians, to find justifications for the sonic abuse that contemporary society is subjected to and to resuscitate, within this vitiated context, the art music meant to re-educate our people, restoring them to the conscience and value of their identity. Educating the public and bringing them closer to contemporary art is a task meant to be fulfilled by music institutions as well, since they should seek to investigate efficient methods of generating connecting bridges to the large masses by transforming music into a shared cultural commodity.